2020
DOI: 10.1039/c9cp06866j
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular hydrogen tunneling in 2-chloromalonaldehyde trapped in solid para-hydrogen

Abstract: Trapping 2-chloromalonaldehyde in solid para-hydrogen is used for a powerful insight into the H-tunneling process at various vibrational levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[ 5 , 9 ] From the theoretical view, the subtle interplay of the partner molecules has significant influence on proton tunneling. [ 10 , 11 , 12 , 13 ] Previous experimental studies have shown that the surrounding environment can modify the proton transfer rate,[ 14 , 15 , 16 , 17 , 18 , 19 ] however, little experimental data is available on how the proton tunneling process is affected by the environment at the few‐molecules level. Herein, we report the direct observation and precise measurement of proton transfer of the formic acid dimer lying on the surface of an aromatic π system.…”
mentioning
confidence: 99%
“…[ 5 , 9 ] From the theoretical view, the subtle interplay of the partner molecules has significant influence on proton tunneling. [ 10 , 11 , 12 , 13 ] Previous experimental studies have shown that the surrounding environment can modify the proton transfer rate,[ 14 , 15 , 16 , 17 , 18 , 19 ] however, little experimental data is available on how the proton tunneling process is affected by the environment at the few‐molecules level. Herein, we report the direct observation and precise measurement of proton transfer of the formic acid dimer lying on the surface of an aromatic π system.…”
mentioning
confidence: 99%
“…[5,9] From the theoretical view, the subtle interplay of the partner molecules has significant influence on proton tunneling. [10][11][12][13] Previous experimental studies have shown that the surrounding environment can modify the proton transfer rate, [14][15][16][17][18][19] however, little experimental data is available on how the proton tunneling process is affected by the environment at the few-molecules level. Herein, we report the direct observation and precise measurement of proton transfer of the formic acid dimer lying on the surface of an aromatic p system.…”
mentioning
confidence: 99%